A Growth‐Promoting Signaling Component Cyclin D1 in Neural Stem Cells Has Antiastrogliogenic Function to Execute Self‐Renewal. (June 2014) - Bizen, Norihisa; Inoue, Toshihiro; Shimizu, Takeshi; Tabu, Kouichi; Kagawa, Tetsushi; Taga, Tetsuya
Abstract: Self‐renewing proliferation of neural stem cells (NSCs) is intimately linked to the inhibition of neuronal and glial differentiation, however, their molecular linkage has been poorly understood. We have proposed a model previously explaining partly this linkage, in which fibroblast growth factor 2 (FGF2) and Wnt signals cooperate to promote NSC self‐renewal via β‐catenin accumulation, which leads to the promotion of proliferation by lymphoid enhancer factor (LEF)/T‐cell factor (TCF)‐mediated cyclin D1 expression and at the same time to the inhibition of neuronal differentiation by β‐catenin‐mediated potentiation of Notch signaling. To fully understand the mechanisms underlying NSC self‐renewal, it needs to be clarified how these growth factor signals inhibit glial differentiation as well. Here, we demonstrate that cyclin D1, a NSC growth promoting signaling component and also a common component of FGF2 and Wnt signaling pathways, inhibits astroglial differentiation of NSCs. Interestingly, this effect of cyclin D1 is mediated even though its cell cycle progression activity is blocked. Forced downregulation of cyclin D1 enhances astrogliogenesis of NSCs in culture and in vivo. We further demonstrate that cyclin D1 binds to STAT3, a transcription factor downstream of astrogliogenic cytokines, and suppresses its transcriptional activity on the glial fibrillary acidic protein (Gfap) gene. Taken together with our previous finding, we provide a novel molecular mechanism for NSC self‐renewal in which growth promoting signaling components activated by FGF2 and Wnts inhibit neuronal and glial differentiation. Stem Cells 2014;32:1602–1615